Factibilidad para la creación de una granja integral en el recinto San Luis del cantón Santo Domingo - Suárez Arboleda, Martha Elizabeth (2012)
The present investigation San Luís carried out in the Enclosure. Km 45+6 route Santo Domingo Quevedo left margin. Parish Santa Maria of the Toachi, Canton Santo Domingo. To a temperature of 24,9 °C, a relative dampness of 88,0 %, rainfall on the level of the sea 2.885,5 Heliofanía year of hours light 629,0. Average annual evaporation 783,7. The same one that will have an approximate duration of 7 months. The primary information was taking of the records of offer and it demands on the national level and later to level of the province of the Tsáchilas in order to organize them across pictures and figures that allow to come to the production of the results to which the respective analysis was applied to them it achieved to determine that the offer is far below of the demand, reason for which He was determined that supply is far below demand, reason why the demand unsatisfied grows significantly progressive. It was a technical, economic and financial study in order to determine the necessary resources for the creation of a comprehensive farm, with the result that can not work with own capital but rather with 60% of funding and 40% provided by social capital. Although this was proposed, only in swine production concludes that it is feasible to carry out this project.